Agrobacterium tumefaciens mediated transformation of sweet potato ( Ipomoea batatas) tuber and regeneration of transformed tissue - Brown, Jonathan Warren (My University, 2016)
Sweet potato (Ipomoea batatasy is one of the six biggest crops in the world, its high nutritional content and large yield in tropical areas making it a useful food source, especially in developing countries. Genetic engineering has the ability to overcome factors such as insect and disease damage which are currently limiting its potential. With this in mind research has been conducted into the development of a protocol to generate transgenic sweet potato from tubers of a local South African cultivar, blesbok. A protocol has been developed which appears capable of generating transgenic plants. Transformation of blesbok tuber tissue was carried out by Agrobacterium tumefaciens mediated transfer of three different binary vectors containing the uidA gene encoding l3-glucuronidase, the npt I 1 gene conferring kanamycin resistance and the bar gene conferring L-phosphinothricin resistance. Long term, stable expression of kanamycin and L-phosphinothricin .resistance was confirmed with kanamycin and Lphosphinothricin screening. Long term, stable expression of l3-glucuronidase was confirmed with fluorescence histochemical studies employing ImaGene Red™. This was further confirmed with quantitative assays of l3-giucuronidase activity using 4· methylumbelliferyl-f-Dcglucuronic acid which showed an average activity of 2.82 nmole.mln'l.mg" protein. Long term, stable integration of uidA into the plant genome was confirmed with polymerase chain reaction amplification screening. Transformed tuber tissue was regenerated via shoot organogenesis to stem structures similarly produced from non transformed tuber tissue. This was achieved for optimised transformation conditions and focused on shoot induction with 2 mg.l" of the auxin 2,4-dichlorophenoxyucetic acid and 0.2 mg.l" of the cytokinin 6-benzylaminopurine. The stems produced still need to be stimulated to develop fully into transgenic plants. This will probably require a sharp increase in the cytokinin.auxin concentration ratio after initial shoot induction.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science, Johannesburg, February 1998.